PENDAMPINGAN KECAMATAN PENGASIH SEBAGAI KPPE (Penataan Sendangsari Menuju Desa Wisata Alam, Seni, dan Kerajinan Tahap I) - Djawadi, Djawadi (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2003)
The goal of the public  service  an the title Assistance  of Pengasih  Subdistrict  Kulon Progo  District   as  the  Sendangsari   Arrangement   to  be  Tourst  Village,  Nature,   Art  and Industry   (Part  I) are: (1) to know  the natural  factor  and society  in Sendangsari   Pengasih Kulonprogo   that  can be developed  into ODTW,  (2) to know  the  desire  and the ability  of the society in Sendangsari  Pengasih  Kulon Pro go that can support  tourism  activities.This public  service  uses sociological-democratic    and anthropological   approach.  The intermediary  target  object  of this public  servise  are tourism  and culture  official  of Kulon progo  District,  the  subdistric  head  of Pengasih,  the  chief  and the  servant  of Sendangsari Village.  Mean  while,  the main  target  are the  famous  figures  of the  Sendangsari   Village. The activity  method  of this public  servise  are visiting  to the Celereng  tourist  spot, touring area and   discussing  target object.The  result  of this  public  service  activity  are:  1) The main  and  intermediary   target support   the   Celereng    Tourist   Spot   Development    Programs.    2)  There   is  Kelompok SadarWiscua  (Pokdarwis)  Sendangsari  established  based on Keputusan  Lurah Desa Sendangsari   nomor  04 tahun  2002  tanggal  16 Agustus   2002.  3) The  activity  programs based  on the meeting  of the servant  team  and the target  object  on August  2, 2002 will be held.  The  servant  team  raises  some  suggestions.    They  are:  1) The  target  object  should monitor   and  evaluate  the  activities   regularly    and  continuously,   so the  program   can  be held  or the plan.  2) This public  service  should  be continued  into part II it can to support the  relizaation   of Kawasan   wisata  Clereng  that  can  increase  the  society  welfare  around the  tourist  spot.  3)  The  intermediary   target  should  increase  the  coordination   with  LPM UNY  (the  servant   team),   so  there   is  no  overlapping   program.   The  programs   should support  each other  depend  on its functions.Key words: tourism village